Penerapan Metode At-Tartil Untuk Meningkatkan Kemampuan Membaca Al-Quran Di TPQ Roudhotul Ulum - Prameswari, Salsa Dea; Fahyuni, Eni Fariyatul (Yayasan Rahmat Islamiyah, 2023)
This research is motivated by the number of children and even teenagers whose ability to read the Quran is still low. There are several factors that influence one of them, namely because of the many types of methods for learning the Quran. With the rapid development of science, especially in the field of education, many practical methods for learning to read the Quran, one of which is the At-Tartil Method. This At-Tartil method is the right choice for anyone who wants to learn the Quran. This study aims to determine how the application of the At-Tartil Method to improve the ability to read the Quran. This research uses descriptive qualitative research. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that: First, learning using the At-Tartil Method is carried out in two times, namely afternoon and evening. Second, there are 3 assessment systems using the At-Tartil Method, namely daily assessment, level assessment / volume increase, and munaqosyah. Third, there are several supporting factors and inhibiting factors in the application of the At-Tartil Method.